The Development of the History Curriculum in English Primary Schools: Analysis of Data and Identification of Trends from the British Historical Association’s 2011 Primary Survey - Jon Nichol; Penelope Harnett (Educational Futures)
Through the 1990 introduction of history as an English National Curriculum subject a Conservative government statutorily embedded history in the English primary curriculum as a de facto new subject. The 1990 English National History Curriculum was a sophisticated blend of three elements: